Tailoring the thermal expansion and electrochemical properties of Pr0.5Ba0.5FeO3-δ electrodes through high-valence cation doping for SOFCs - Sánchez Caballero, Abraham; Dos-Santos-Gómez, Lucía; Zamudio-García, Javier; Porras-Vázquez, José Manuel; Marrero-López, David (Elsevier, 2025)
This study explores how high-valence dopants affect the structural, thermal, and electrochemical properties of (Pr0.5Ba0.5)0.98Fe0.9M0.1O3-δ (M = Ga3+, Ti4+, Zr4+, Nb5+, Mo6+, W6+, and Re7+) for SOFC air electrodes. Thermogravimetric analysis reveals that increasing the dopant oxidation state reduces oxygen loss upon heating, indicating improved stability of the oxygen sublattice. Consistently, dilatometric measurements show a decrease in the thermal expansion coefficients from 22.3 × 10-6 K-1 for Ga3+-doped to 15.1 × 10-6 K-1 for W6+-doped samples. Impedance spectroscopy further confirms a clear correlation between dopant oxidation state and electrode polarization resistance, with values slightly increasing from 0.14 Ω cm2 for (Ga3+) to 0.21 Ω cm2 (W6+) at 700 ºC. These findings demonstrate that while high-valence doping improves structural stability and reduces thermal expansion, it does not necessarily enhance the oxygen reduction reaction activity. Overall, this study provides key insights into doping strategies to optimize SOFC air electrodes by balancing stability, thermal compatibility, and performance.
https://openpolicyfinder.jisc.ac.uk/id/publication/13247
PID2021-126009OB-I00 TED2021-129836B-I00
Keywords: Pilas de combustible; Conversión directa de la energía; SOFC; Air electrode; PrBaFe2O5+δ; Oxygen deficiency; Thermal expansion